Organic Matter in Carbonaceous Mineral Waters of the Shmakovka Field, Far East, Russia - Poturay, V. A. (Geochemistry international, 2025)
Original data were obtained on the composition and content of medium-volatility organic compounds in cold carbonaceous mineral waters from the Shmakovka deposit in Primorsky Krai. Using capillary gas chromatography–mass spectrometry and solid-phase extraction, a number of organic components forming 16 homologous series were identified. The results revealed the predominance of aliphatic hydrocarbons (mainly normal alkanes and isoalkanes) in the carbonaceous waters, accounting for more than half of the total organic compounds. The remaining compounds include oxygen-containing and aromatic compounds, with the latter being present in minor amounts. Based on the molecular weight distribution of saturated hydrocarbons, the organic matter in the studied waters is of bacterial origin. The presence of aromatic hydrocarbons is likely due to the action of supercritical CO 2 . Additionally, one of the Shmakovka field sites is likely subject to anthropogenic pressure, as indicated by the presence of chlorinated hydrocarbons and elevated phthalate concentrations.